On bitumen microstructure and the effects of crack healing - Gaskin, Joshua (2013)
When an asphalt pavement is subjected to repeated traffic loads punctuated by rest periods, the acquisition of damage is interrupted by molecular relaxation and healing: the restoration of continuity across fractured interfaces. The healing effect is responsible for improved fatigue performance at high temperatures and dominates the laboratory-to-field shift factor in design. The mechanism of healing is not well understood, however. To describe this process, myriad investigations are collated with healing in high polymers, but neglect microstructural changes due to the damage processes that precipitate fracture. Yet, the remnants of deformation drive healing phenomena. An enhanced knowledge of healing and the effect of fracture could allow for the direct application of laboratory fatigue in pavement performance prediction.